2014
DOI: 10.1108/ijhcqa-04-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Patient-clinician concordance, face-time and access

Abstract: Applying RTLS to healthcare is coming. We can now successfully install and run these systems in healthcare settings and extract useful information from them. Interactions with the clinical delivery system are at least as important as interactions with clinicians for providing access to care: measure FT, WT and FLT with RTLS; link clinical behavior, e.g. FT, with patient characteristics; explore how individual characteristics interact with system behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…More than in other services, as, for example, financial services or connected to tourism, quality is more complex to be defined in health because it considers people's lives and the main influences for service users analyses hovers on professionals cordiality, competence, time spent (attention) with the patient and the quantity of provided information. Patients look for support behaviors, effectiveness, care, help and attention by health service providers (Naidu, 2009;Bergström et al, 2013;Stahl, Drew & Kimball, 2014), directly impacting on their service satisfaction level (Larsson & Wilde-Larsson, 2010). From direct observation and the interview performed with the Obstetric Center obstetric doctor, it was found that some infrastructure changes, in operational processes and people management could positively influence service quality perceived level and, consequently, obstetric users satisfaction level.…”
Section: Final Considerationsmentioning
confidence: 99%
“…More than in other services, as, for example, financial services or connected to tourism, quality is more complex to be defined in health because it considers people's lives and the main influences for service users analyses hovers on professionals cordiality, competence, time spent (attention) with the patient and the quantity of provided information. Patients look for support behaviors, effectiveness, care, help and attention by health service providers (Naidu, 2009;Bergström et al, 2013;Stahl, Drew & Kimball, 2014), directly impacting on their service satisfaction level (Larsson & Wilde-Larsson, 2010). From direct observation and the interview performed with the Obstetric Center obstetric doctor, it was found that some infrastructure changes, in operational processes and people management could positively influence service quality perceived level and, consequently, obstetric users satisfaction level.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Ohashi et al demonstrated in a pilot project that an RTLS could reduce the time nurses spent performing verification tasks. [13][14][15][16] Stübig et al showed that a Wi-Fi-based RTLS decreased treatment time for outpatients by 23%. 17 Stahl et al evaluated an RFID system in a primary care facility and found mixed results.…”
Section: Background and Significancementioning
confidence: 99%